Penerapan Vertikal Mixer Adonan 10 Kilogram Dalam Peningkatan Produksi Ukm Kerupuk Pangsit - Lilin Hermawati; Sugeng Haryadi; Padang Yanuar; K Kundori; Iman Mujiarto (Jurnal TUNAS, 2020)
There are still many dumpling cracker makers who are generally done at home as a small home industry where they still use human labor to make the dough so that it takes a lot of energy and a long time, the use of human labor causes a lack of time efficiency and the possibility of decreased hygiene. Seeing these problems, the community service team of the D3 Engineering study program at the Maritime University of Amni Seamarang provided solutions to these problems by designing tools and providing training in the operation of the dough mixer to accelerate the production process and increase the hygienic value of production. The result of this service is a double stirring of the dumpling cracker dough which increases the speed of the kneading production process for 30 minutes / dough.